Multi-stage e-delphi-trade off analysis for quality-based management system at Tra Vinh University - Đặng Diệp Minh Tân (Southern Leyte State University, 2022)
This study aimed to develop a quality-based management system in the training process of Tra Vinh University. This system is composed of factors influencing its implementation, the manners in which internal stakeholders contribute to its implementation, components that directly and indirectly contribute in creating the training quality of Tra Vinh University, and the foundation mechanism to maintain and continuously improve the training quality at Tra Vinh University as recommended by the TVU internal stakeholders.